Glucose concentration affects recombinant interferon α-2b production in Escherichia coli using thermo-induction system - Mesalhy S. Mansey, Kamel A. Ghareeb, Abdel Naser Moghazy, Mahmoud M. Tawfick,Mohamed M. Fouda, NagibA. El Marzugi, Nor Zalina Othman, Hesham A. El Enshasy , (Journal of Applied Pharmaceutical Science, 2014)
In the present work, a recombinant Escherichia coli strain was used for the production of interferon α-2b in both shake flask and in bioreactor. The first part of this research was focused on the investigation of the effect of glucose concentration on the kinetics of cell growth, recombinant protein production and acetate formation. In general, glucose supplementation to culture medium enhanced cell growth when added in concentration between 0-20 g/L. Further increase in glucose level reduces biomass production and enhances acetate accumulation in culture. The results clearly demonstrated that maximal interferon production of 27.7 mg/L was achieved in culture supplemented with 20 g/L glucose. Further improvement in recombinant interferon production process was also achieved by scaling up from shake flask to 16-L stirred tank bioreactor. The maximal volumetric interferon production in bioreactor batch culture was 44.5. mg/L after only 6 hours.
Keywords: rEscharichia coli,interferon &alpha; -2b,batch cultivation,glucose effect,bioreactor cultivation.